Supervisory Roles in Loan Loss Provisioning in Countries Implementing IFRS - Gaston, Ellen; Song, In. (Washington, D.C. : International Monetary Fund, 2014)
Countries implementing International Financial Reporting Standards (IFRS) for loan loss provisioning by banks have been guided by two different approaches: International Accounting Standards (IAS) 39 and Basel standards. This paper discusses the different accounting and regulatory approaches in loan loss provisioning, and the challenges supervisors face when there are different perspectives and lack of guidance from IFRS. It suggests actions that supervisors can take to help banks meet regulatory and capital requirements and, at the same time, comply with accounting principles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet